Consequences of Lack of Neonatal Breastfeeding in Infants Hospitalized for Diarrhea at an Urban Hospital, Bangladesh: A Case Control Design. (May 2019) - Shahid, Abu S. M. S. B.; Ahmed, Tahmeed; Kabir, Senjuti; Huq, K. A. T. M. Ehsanul; Shahunja, K. M.; Faruque, Abu Syeed Golam; Rahman, Md Moshiur; Islam, Md Munirul; Chisti, Mohammod Jobayer
Background . Exclusive breastfeeding is important for immunity and lack of breastfeeding during the neonatal age impedes that. Our aim was to assess the consequences of lack of breastfeeding on infants with diarrhea in the neonatal period. Methods . In this design, infants from DDSS (Diarrheal Disease Surveillance System) from 2009 to 2013 were studied. Those who did not have breastfeeding or had cessation of breastfeeding at the neonatal age constituted the cases, whereas infants who continued breastfeeding since birth or for at least 6 months since birth constituted the controls. Results . The cases more often presented at a younger age, had an illiterate mother, frequently presented with complicated diarrhea, had severe wasting, and had abnormal mental status compared with the controls. In logistic regression, after adjusting for potential confounders, infants who lacked breastfeeding at the neonatal period had an independent association with dehydrating diarrhea. Conclusions . The results of our analyses suggest that infants with diarrhea who did not have breastfeeding at the neonatal age are prone to develop some or severe dehydration.